Current perspectives in drug targeting intrinsically disordered proteins and biomolecular condensates - Caolitao Qin; Yun-Long Wang; Jian Zheng; Xiang-Bo Wan; Xin-Juan Fan (BMC Biology)
Abstract Intrinsically disordered proteins (IDPs) and biomolecular condensates are critical for cellular processes and physiological functions. Abnormal biomolecular condensates can cause diseases such as cancer and neurodegenerative disorders. IDPs, including intrinsically disordered regions (IDRs), were previously considered undruggable due to their lack of stable binding pockets. However, recent evidence indicates that targeting them can influence cellular processes. This review explores current strategies to target IDPs and biomolecular condensates, potential improvements, and the challenges and opportunities in this evolving field.